A Conceptual MIS Framework for Business Intelligence - Mian, Tariq Saeed (International Journal of Management Innovation Systems, 2024)
The prime objective of the present study was to examine the relationship between compatibility, top management support, competitive pressure and organizational performance with the mediation of business intelligence. The data in the present study were collected from the employees of Madina grocery store by purposive sampling. The response rate of the study was 69%. The collected data was analysed through smart PLS 3.3.2. The results of the study revealed that competitive pressure, top management support and compatibility have a positive effect on business intelligence and organizational performance. Additionally, the mediation result of business intelligence is also confirmed by the results of the present research. This research fills the gap between limited studies regarding business intelligence and organizational performance. This study is helpful for the decision-makers of management of different organizations.